Pengembangan Media Pembelajaran Augmented Reality (AR) menggunakan Model ADDIE pada Materi Haji Umrah di Madrasah Ibtidaiyah - Pratama, Havidz Cahya; Yaqin, Ainul; Wartono, Wartono; Septiana, Ambar (Universitas Muhammadiyah Magelang, 2026)
Technological advancements require educators to be able to utilize innovative learning media that are engaging, interactive, and enjoyable for students. One technology with strong potential to support learning is Augmented Reality (AR). This study aims to develop an AR–based learning medium for the Hajj and Umrah material and to examine students’ responses to its use at MI Muhammadiyah Limbangan Purbalingga. This research employed the Research and Development (R&D) method using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data analysis techniques were conducted using descriptive quantitative methods to process student response questionnaires and descriptive qualitative methods to interpret feedback obtained during the development process. The results indicate that the developed AR–based learning media are able to provide a more interactive and enjoyable learning experience and increase student engagement in learning the Hajj and Umrah material. Student responses to the use of this media fall into the very attractive category. Therefore, AR–based learning media are feasible to be used as an alternative innovation in teaching Hajj and Umrah at the madrasah ibtidaiyah level.